Online Professional Learning Networks (OPLNs) Integrated to the Community of Inquiry (CoI) Model: Basis for Professional Development for Teachers - Cerna, Lovirey (Journal of Interdisciplinary Perspectives, 2024)
The findings of the Programme for International Student Assessment (PISA) revealed a significant concern: where Philippine school principals agreed or strongly agreed that teachers possessed the necessary technical and pedagogical skills to integrate digital devices into education, they also reported that a shortage of teaching staff hindered the school's capacity to provide instruction. This study assessed the perceived impact of Online Professional Learning Networks (OPLNs) integrated to the Community of Inquiry (CoI) framework on teacher professional development. Using a descriptive design, the study explored the impact of demographic profiles on OPLNs and their integration into the CoI model. The findings revealed that participation in OPLNs did not differ significantly based on respondents' demographic profiles. However, participation in OPLNs significantly impacted teaching performance, particularly in the CoI elements of "Teaching Presence" and "Cognitive Presence." However, the "Social Presence" element had no significant impact following OPLN integration. The prevalence of "Strongly Agree" ratings in the OPLNs sub-categories—Motivation, Design, and Sharing and Learning—highlighted OPLNs' effectiveness in promoting continuous learning and active participation among teachers. This suggests the vitality of ongoing professional development and positions OPLNs as effective tools for addressing issues such as limited opportunity for worldwide collaboration and interdisciplinary expertise. To receive the most benefits from OPLNs, educators and administrators should prioritize improving teaching and cognitive presence by encouraging critical thinking and facilitating organized discussions. These approaches have proven essential in improving educational outcomes and experiences. Furthermore, additional research should look into novel ways to improve "social presence" in OPLNs, such as including interactive elements, encouraging collaboration, and cultivating a supportive online community to increase learning satisfaction and engagement.